Influence of Proactive Personality on Turnover Intention among Hotel Employees: Perceived Organizational Support as A Moderating - Aurilia Triani Aryaningtyas (Journal of Business and Management Review, 2022)
This study conceptualizes the perceived organizational support (POS) as a moderator to understand the mechanism of the relationship between proactive personality and turnover intention. This study proposes a different model of proactive personality as a variable that affects the turnover intention of hotel employees, which in turn is related to POS as a moderating variable. This influence model has never been studied on hotel employees, especially in Semarang. Some researchers tend to explore the influence of factors such as job satisfaction, job stress, citizenship behavior, and commitment. The effect moderation model in this study was examined using multilevel regression analysis, with an interaction test which is often called Moderated Regression Analysis (MRA). By quota sampling technique, survey data collected from 200 hotel employees spread across Semarang city. The results showed that the influence of proactive personality and turnover intention was weaker when perceived organizational support was included in the interaction. These findings are consistent with existing theories and studies. The implications for management practice suggest hotel managers to consider perceived organizational support as a fairly important factor in encouraging proactive employees to minimize intention to leave their current job.